Peran Notaris dalam Pengikatan Perjanjian Kredit yang Diikuti dengan Jaminan Surat Berharga - Nurul Jinan (Syntax Idea)
The implementation of binding credit agreements, especially in banking matters, generally uses an authentic deed drawn up by a notary as a perfect means of proof. The provision of credit followed by special guarantees has different characteristics depending on the type of collateral provided by the debtor. Therefore, the role of the Notary is not only limited to the credit agreement but also in the guarantee binding process. The purpose of this legal research is to determine the scope of duties, authorities and the role of a Notary in the implementation of credit agreement followed by a mortgage guarantee in the form of securities. This legal research is normative legal research. The data collection tool used was a literature study with due regard to primary legal materials in the form of laws and regulations and secondary legal materials, namely books, journals and other library materials related to this research. The results of the study show that securities that are used as a collateral for credit may be made with a pawn or fiduciary system depends on the object served by debtor. If the bond binding is carried out with the fiduciary system, the role of the Notary is very important considering that the fiduciary guarantee deed required to be made in the authentic deed.